Using Bioremediation to Reduce Groundwater Salinity - Rashid, Rawaa Hamid Abdul; Ghazal, Kareem A. (Journal of Tropical Crop Science, 2026)
A study was conducted to evaluate the effectiveness of microorganisms in reducing groundwater salinity and to identify the most effective organisms. A laboratory experiment was performed using a completely randomised block design with a factorial arrangement, with four treatments and three replicates, yielding 12 experimental units for the biological treatment of groundwater. This experiment included the sequential addition of microorganisms (control, Providencia rettgeri, Bacillus amyloliquefaciens, and Rhizoctonia solani) to groundwater with a salinity of 13108 µS/cm, with continuous monitoring of changes in EC, pH, and other water chemical properties. Providencia rettgeri achieved the highest temperature on June 26th, reaching 29.0 °C, whereas the control treatment recorded a lower temperature on the same date. Meanwhile, Bacillus amyloliquefaciens outperformed the control, achieving the highest nitrogen content in the treated water at 1499 mg/L, compared with the control at 1372 mg/L. Rhizoctonia solani excelled by recording the lowest electrical conductivity and pH for the treated water on 6/25, at 11607 ds/cm and 6.73, respectively, compared to the control treatment, which recorded the opposite in both characteristics.